(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
The purpose of this study was to examine the relationship between creativity and mental illness, discussing their psychological and social implications. This allows us to reflect on how creativity is valued and accepted in our society and how stereotypes involving highly creative people influence their trajectory of life. Based on the literature in the field of creativity, we discussed the concept of creativity and mental disorder and sought to analyze the interrelationship between the two constructs. It can be concluded that there is no consensus about this association. Such divergences can be explained by the absence of a specific definition of the constructs, and the need to determine which disorder was investigated and in relation to which dimension of creativity. It is not a direct, causal, simplistic or global relationship. We also discuss how social patterns determine and differentiate the highly creative individual from those who exhibit deviant behavior.